First use of whole‐genome sequencing to investigate a cluster ofYersinia enterocolitica, Liverpool, United Kingdom, 2017. Issue 12 (December 2018) - Inns, Thomas; Flanagan, Stephen; Greig, David R.; Jenkins, Claire; Seddon, Keeley; Chin, Toong; Cartwright, Joanna
Abstract : Purpose. : In May 2017 we were notified of a cluster of Yersinia enterocolitica ‐positive isolates from Liverpool. The purpose of this work was to investigate this cluster of cases and find a possible common source. We combined epidemiological information with whole‐genome sequencing (WGS) results, which indicated that these cases were unlikely to be from the same source. This investigation provides evidence that WGS could be used to investigate future clusters of Y. enterocolitica cases. Methods. : A case was defined as a person with a laboratory‐confirmed isolate of Y. enterocolitica, sampled in 2017, who is a resident in Liverpool local authority at the time of sampling. Faecal samples were cultured at the local laboratory and presumptive isolates of Yersinia sp. were identified using matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS). Positive isolates were whole‐genome sequenced by the reference laboratory. Results. : Nine cases were identified, which was significantly greater ( P <0.0001) than the average number of cases in this area from the last 10 years. Six cases were female (66.67 %) and the ages of the patients ranged from 20 to 81 (median 54). The sample dates ranged from 29 April to 1 August 2017. The WGS results showed that Y. enterocolitica isolates belonged to different sequence types. Conclusion. : This was the first time that WGS was used to investigate a cluster of Y. enterocolitica cases; the cases were clustered in time, person and place, but the WGS results indicate that these cases were not from the same source. This result informed the Outbreak Control Team's decision‐making and resulted in the investigation being closed.